2018
DOI: 10.2196/11294
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Biological and Functional Changes in Healthy Smokers Switching to the Tobacco Heating System 2.2 Versus Continued Tobacco Smoking: Protocol for a Randomized, Controlled, Multicenter Study

Abstract: BackgroundTobacco harm reduction, substituting less harmful tobacco products for combustible cigarettes, is a complementary approach for smokers who would otherwise continue to smoke. The Philip Morris International (PMI) Tobacco Heating System (THS) 2.2 is a novel tobacco product with the potential to reduce the risk of harm in smokers compared to continued smoking of combustible cigarettes. It heats tobacco electrically in a controlled manner, never allowing the temperature to exceed 350°C, thereby preventin… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 36 publications
0
5
0
Order By: Relevance
“…In line with these findings, the combination of nicotine and other harmful compounds in smoke and vape is one of the most likely explanations for the effects on the cardiovascular system 10 and lungs. 3,11,12 These components might also trigger an endothelial dysfunction and an increase of arterial stiffness, which might trigger cardiovascular events. 13 The first limitation of our study is the number of subjects who were studied.…”
mentioning
confidence: 99%
“…In line with these findings, the combination of nicotine and other harmful compounds in smoke and vape is one of the most likely explanations for the effects on the cardiovascular system 10 and lungs. 3,11,12 These components might also trigger an endothelial dysfunction and an increase of arterial stiffness, which might trigger cardiovascular events. 13 The first limitation of our study is the number of subjects who were studied.…”
mentioning
confidence: 99%
“…The magnitude of reduction was comparable to that observed in smokers who abstained from smoking, which has been referred to as the "gold standard" for the assessment of candidate reduced risk products [42,43]. Longer exposure studies of at least 6 months have shown favorable biological changes in smokers switching to THS, thereby reflecting improvement of several pathophysiological pathways that may eventually lead to the development of tobacco-related diseases, such as inflammation, oxidative stress, or endothelial dysfunction [44,45]. Preclinical data on gingival [46] and oral epithelial [47] human organotypic cultures showed minor histopathological alterations and minimal cytotoxicity upon THS aerosol exposure compared with exposure to cigarette smoke as well as a very significantly reduced overall impact, as illustrated by the measurement of inflammatory mediators and by transcriptomic and metabolomic analyses.…”
Section: Introductionmentioning
confidence: 94%
“…Phillip Morris’s clinical and aerosol outcome data are not comprehensive, and in fact 56 potentially harmful substances are higher in IQOS aerosol than cigarette smoke. 6 12 Concerns about Phillip Morris’s IQOS research 13 14 and failure to make data from its longer term studies public 15 16 are amplified by the tobacco industry’s history of research manipulation and hiding the harms of smoking. 13 17 With the many other products now available, including pharmaceutical nicotine, which are known to be safe, smokers looking to reduce harm rather than quit should see heated tobacco products as a last resort.…”
Section: Minefieldmentioning
confidence: 99%